Music, Persecution and the Freedom of the Soul: Songs of Transcendence in Marnix's Het Boeck der Psalmen Dauids (1580) - Kim, Hyun-Ah (Kerk en theologie, 2023)
This article explores how metrical psalmody as a form of musical poetry was utilised to relieve mental, physical and emotional turmoil which early-modern religious prisoners and refugees underwent, focussing on Philips van Marnix's Boeck der Psalmens Dauids (1580). By situating Marnix's psalm versification within the context of Renaissance Biblical humanism where music and poetry are inseparable, the article seeks to determine the place of Marnix in the history of religious poetics contributing to early Protestant devotional practices, in which the psalmody served as the songs of transcendence, freeing the soul from persecution and, ultimately, from the death of the body.